Nilai Karakter dalam Majalah Bobo dan Relevansinya sebagai Media Pembentukan Kecerdasan Ekologis - Henry Trias Puguh Jatmiko; Sakrim Sakrim; Dimas Adika; Liyana Dian Prastiwi (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2026)
This study aims to describe the character values found in Bobo magazine and explore their relevance as a medium for character development among Generation Alpha. The research method used in this study is qualitative descriptive. The data consist of documents, specifically short stories published in Bobo magazine. Data were collected through observation and note-taking. The data were then validated using theoretical triangulation, followed by analysis using a flow model. The results of this study indicate that Bobo magazine contains six character values, including honesty, tolerance, democracy, curiosity, and friendship. These values not only build character intelligence but also contribute to ecological intelligence.